Culturally responsive leadership: a critical analysis of one school district’s five-year plan - Mansfield, Katherine Cumings; Lambrinou, Marina (Frontiers in Education, 2024)
Centering the need for culturally responsive leadership (CRL), this study engages in a critical analysis of one large urban school district's 5-year plan that aims to be culturally responsive and equity focused. We first define the various facets of CRL, connect its major components to culturally responsive teaching/pedagogy (CRTP) and student voice (SV), and offer an original, integrative framework as a tool for analysis. We argue that CRL is not enough on its own and needs more than the commitment of principals to reach its maximum potential. We also provide recommendations on what needs to happen to make culturally responsive schooling a reality for students and their communities.